2019
DOI: 10.3389/fimmu.2019.01931
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Approaches for the Diagnosis of Autoimmune/Autoinflammatory Skin Diseases—A Focus on Psoriasis and Lupus erythematosus

Abstract: The traditional diagnostic gold standard for inflammatory skin lesions of unclear etiology is dermato-histopathology. As this approach requires an invasive skin biopsy, biopsy processing and analysis by specialized histologists, it is a resource intensive approach requiring trained healthcare professionals. In many health care settings access to this diagnostic approach can be difficult and outside emergency cases will usually take several weeks. This scenario leads to delayed or inappropriate treatment given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 138 publications
(130 reference statements)
0
24
0
Order By: Relevance
“…In striving for this perfect balance, there is a need for a better system to monitor for signs of rejection while using minimal immunosuppression [26][27][28][29] Cytokine detection in skin has long been used to evaluate for presence of different skin conditions. Grellner et al found that IL-1b was detectable at increased levels in early injury, whereas TNF-a was increased after 1-2 h and IL-6 after 24 [30] In inflammatory pathology, cytokines are even more extensively demonstrated to be altered from the control in the setting of different conditions [31][32][33][34] These studies give more credence to the concept that identification of dermal inflammatory markers is useful in the care of patients with skin disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In striving for this perfect balance, there is a need for a better system to monitor for signs of rejection while using minimal immunosuppression [26][27][28][29] Cytokine detection in skin has long been used to evaluate for presence of different skin conditions. Grellner et al found that IL-1b was detectable at increased levels in early injury, whereas TNF-a was increased after 1-2 h and IL-6 after 24 [30] In inflammatory pathology, cytokines are even more extensively demonstrated to be altered from the control in the setting of different conditions [31][32][33][34] These studies give more credence to the concept that identification of dermal inflammatory markers is useful in the care of patients with skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…As well, there have been multiple studies showing that biopsies themselves can actually incite immune responses, thereby causing the specific reaction that they are meant to monitor to help prevent [18,19,35] Alternatively, tape stripping does not require anesthetic, does not carry the risk of scarring as seen with biopsies, and can be performed repeatedly directly on the lesion or area of interest. As a technique, tape stripping has been well shown to be able to detect protein including specific cytokines through the superficial epidermis [34] Pro-inflammatory cytokines in nontransplant conditions have been shown to be detectable using the method [36] As a small sample, Morhenn et al were able to distinguish irritant pathology from immunologic reaction using tape-stripping detection of cytokine mRNA [22] Perkins et al used tape-stripping and ELISA analysis to detect IL-1a, IL-1Ra, TNFa, and IL-2, and a group out of the United Kingdom has shown that detection of specific cytokines including CXCL1, IL-8, CCL20, and IL36c was possible by tape stripping, with IL-36c showing promise for differentiating specific inflammatory immune responses [37] In VCA, cytokine presence in graft skin has been shown to be associated with graft rejection. Kollar et al utilized an aptamer-based SOMAscan proteomics platform to show alterations in a 5-protein signature during rejection episodes and detected a specific increased in metallopeptidase (MMP3) activity during severe rejection of face transplant [38] The Innsbruck group showed different gene expression of IL-12b, IL-17, and IL-1b in rejection and inflammation of VCA, with CCL7, IL-18, and IL-1b expression being the most indicative of a rejection pathology [39] Though noninvasive methods have been studied -SOMAscan [38], ultrasound biomicroscopy [40] to our knowledge, no human-based studies using tape stripping in VCA have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this case, the obtaining of the hair follicles in the OCT images would be useful to study the changes in follicular volume and size produced by cancerous effects. The follicular structures are also the main target in a subtype of cutaneous lupus erythematosus (LE) called chronic discoid LE (CDLE), which results in an irreversible hair loss due to the recruitment of the cells to the bulge region of the hair follicles coupled with the collapse of immune privilege ultimately (17).…”
Section: Discussionmentioning
confidence: 99%
“…This result agrees with the result obtained by Khmaladzeet al in Istanbul who studied the oxidative stress status in patients with psoriasis in comparison with healthy controls [28] . As well as Erdem, et al [29] and Anna, et al [30] who studied the role of oxidative stress and inflammation response in psoriasis patients and with Lai, et al who studied the role of oxidative stress at various stage of psoriasis in Indian patients [31] .…”
Section: Health Annals Of Tropical Medicine and Publicmentioning
confidence: 99%